FORMULATION AND EVALUATION OF GASTRORETENTIVE FLOATING TABLET USING HIBISCUS ROSA-SINENSIS MUCILAGE - RS, KHARWADE; SM, MORE; Un, Mahajan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: Domperidone is a synthetic benzimidazole compound that acts as a dopamine D2 receptor antagonist. The main aim of this study was to optimize and evaluate the floating tablets of domperidone that prolongs the gastric residence time using Hibiscus rosa-sinensis mucilage. Methods: The directly compressible floating tablets of domperidone were formulated using varying amount of hydroxypropyl methylcellulose K100 M, carbopol 934P and H. rosa-sinensis mucilage. The effervescent components sodium bicarbonate is used for the generation of CO2 gas. The prepared tablets were evaluated for physicochemical parameters and found to be within range, viz., hardness, swelling index, floating capacity, thickness, and weight variation. Further, tablets were evaluated for in vitro release characteristics. The concentration of H. rosa-sinensis mucilage with a gas-generating agent was optimized to get the sustained release of domperidone. Result: The % cumulative drug release of all formulation from F1 to F6 was within the range of 81.37% to 98.62% for 18 hrs. The release kinetics of all the dosage forms was calculated using zero order, first order, Higuchi, and Korsmeyer–Peppas. It concludes that the release followed zero order release, whereas the correlation coefficient (r2 value) was higher for zero order release. The release mechanism follows Higuchi model, Korsmeyer- Peppas model, and non-Fickian diffusion. Conclusion: As a result of this study, it may be concluded that the floating tablets using H. rosa-sinensis mucilage in optimized concentrations can be used to increase the gastric retention time of the dissolution fluid in the stomach to deliver the drug in a sustained manner. Furthermore, from 1 month stability data shows no significant change compared to initial result. Keywords: Floating drug delivery, Hibiscus rosa-sinensis mucilage, Domperidone.